Introduction to comparative politics - Stewart, Michael [author.]
"This book Comparative Politics serves as a critical tool for comprehending the global political landscape. It allows scholars, students, and policymakers to gain insights into the diverse array of political systems, practices, and challenges that nation face, ultimately contributing to a deeper understanding of the complex world of politics." -- Provided by the publisher